SISTEM PENDUKUNG KEPUTUSAN UNTUK KLASIFIKASI RUMAH TANGGA MISKIN INI - Andri Sukmaindrayana; Akik Hidayat (LPPM STMIK DCI, 2015)
Since the implementation of regional autonomy, the term village can be called by other names, for example in West Sumatra called the villages, and in Papua and West Kutai, East Kalimantan, called the village. Similarly, all the terms and institutions in the village can be called by other names in accordance with the customs of the characteristics of the village. This is one of recognition and respect to the origin of the Government and local customs.According to Law No. 32 of 2004 and Government Regulation No. 72 of 2005 on the village, mentioned that the village is a unit of community that has boundaries with the authority to regulate and manage the interests of the local community, based on the origin and the local customs are recognized and respected in the administration system of the Republic of Indonesia.The village is not subordinate districts, because the sub-district is part of the district / city, and the village is not part of the area. Unlike the village, the village has the right to regulate the wider region. But in its development, a village can be converted into a village status.That in an effort to realize the implementation of democratic governance in the village to be able to mobilize the community to participate in the development and the administration of the village, then any policy decision taken into account local conditionsKeyword : Village, Local Community, Policy Decision Taken.